Theoretical Aspects of the Term Parameterization in Modern Linguistics (Proceedings of Southern Federal University. Philology, 2017)
Susanna R. Tlekhatuk (Maykop, Russian Federation)The term specific character as a specialized sign of language and science is considered in the article. The term is a unit of cognition and simultaneously serves as a unit of nomination of its results. The author advances an idea that, representing a special notion by means of a language sign, the term becomes cognitive semiotic instrument of cognition. The author of the article states that the definition is an essential characteristic of the term playing an important role in singling out terminological lexis from the word stock of a language. Multidimensional characteristic and derivational complexity of a scientific term is exposed in the article.Key words: object domain, term, science of terminology, definition, content accuracy, sign, notion, cognition.DOI 10.23683/1995-0640-2017-3-165-169